National Cancer Database report of nonmetastatic esophageal small cell carcinoma. (6th November 2018) - Verma, Vivek; Sleightholm, Richard L.; Fang, Penny; Ryckman, Jeffrey M.; Lin, Chi
Abstract: Background: Esophageal small cell carcinoma (ESCC) is a rare malignancy for which there is no consensus management approach. This is the largest known analysis of nonmetastatic ESCC patients to date, evaluating national practice patterns and outcomes of surgical‐based therapy vs chemoradiotherapy (CRT) vs chemotherapy alone. Methods: The National Cancer Data Base was queried for esophageal cancer patients with histologically confirmed nonmetastatic ESCC. Univariable and multivariable logistic regression ascertained factors associated with receipt of surgical‐based management. Kaplan‐Meier analysis evaluated overall survival (OS) and the log‐rank test is used to compare OS between groups; Cox univariate and multivariate analyses determined variables associated with OS. Results: Altogether, 323 patients were analyzed; 64 (20%) patients underwent surgical‐based therapy, 211 (65%) CRT, and 48 (15%) chemotherapy alone. On multivariable analysis, no single factor significantly predicted for administration of surgery. Despite no OS differences between the surgery‐based (median OS 21 months) and CRT arms (18 months), both were superior to CT alone (10 months) ( P  < 0.001). Among other factors, receiving any local therapy independently predicted for higher OS over chemotherapy alone on Cox multivariate analysis ( P  < 0.001). Conclusions: This study of a large, contemporary national database demonstrates that most ESCC is treated with CRT in the United States; adding local therapy to systemic therapy may be beneficial to these patients, although individualized multidisciplinary management is still recommended. Abstract : Because the study of rare neoplasms, such as ESCC is highly limited by sample size and heterogeneity in existing reports, it is essential to perform large‐volume investigations of homogeneous patients. This study of a large, contemporary national database demonstrates that most ESCC is treated with CRT in the United States; adding local therapy to systemic therapy may be beneficial to these patients, although individualized multidisciplinary management is still recommended.